2021
DOI: 10.1111/tpj.15409
|View full text |Cite
|
Sign up to set email alerts
|

Ectopic expression of an expansin‐like B gene from wild Arachis enhances tolerance to both abiotic and biotic stresses

Abstract: Plant expansins are structural cell wall-loosening proteins implicated in several developmental processes and responses to environmental constraints and pathogen infection. To date, there is limited information about the biological function of expansins-like B (EXLBs), one of the smallest and less-studied subfamilies of plant expansins. In the present study, we conducted a functional analysis of the wild Arachis AdEXLB8 gene in transgenic tobacco (Nicotiana tabacum) plants to clarify its putative role in media… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 69 publications
(135 reference statements)
1
10
0
Order By: Relevance
“…Plant expansins are involved in cell wall loosening and are active components of stress-associated responses, commonly related to defense priming processes [ 8 , 57 ]. Moreover, the upregulation of EXLB and EGC genes is consistent with our recent findings that the overexpression of an A. duranensis EXLB gene enhanced tolerance to abiotic and biotic stresses by mediating the induction of a defense primed state [ 100 ].…”
Section: Discussionsupporting
confidence: 90%
“…Plant expansins are involved in cell wall loosening and are active components of stress-associated responses, commonly related to defense priming processes [ 8 , 57 ]. Moreover, the upregulation of EXLB and EGC genes is consistent with our recent findings that the overexpression of an A. duranensis EXLB gene enhanced tolerance to abiotic and biotic stresses by mediating the induction of a defense primed state [ 100 ].…”
Section: Discussionsupporting
confidence: 90%
“…Conversely, very few reports showed the involvement of α-Expansins in both compatible and incompatible plant-microbe interactions [ 35 , 72 76 ]. Recently, some studies also demonstrated the putative role of the Expansin superfamily in mediating resistance responses to simultaneous abiotic and biotic stresses (cross-stress) as well as in defense priming processes and stress memory [ 35 , 77 81 ]. Our findings support those studies by showing that AdEXPA24 overexpression improves resistance against Meloidogyne sp.…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned before, signs of cell wall modification due to microbial activity or induced by abiotic stress are detected by membrane receptors alerting the cell to mount defense and stress responses, sometimes simultaneously. For instance, ectopic overexpression of EXLB8 from Arachis in tobacco results in tolerance to water deficit and resistance to the white mold causative necrotrophic fungus [ Sclerotinia sclerotiorum ( Hegedus and Rimmer, 2005 )], and to the nematode M. incognita , and to drought and simultaneous nematode infection ( Brasileiro et al, 2021 ). Different cell wall nanomechanical properties (possibly stiffer, but more deformable leaves), brought about by EXLB8 overexpression, and consequently, possibly by other six endogenous EXL genes, was suggested as responsible of the phenotype hampering a successful infection.…”
Section: Expansins In Susceptibility To Infectionmentioning
confidence: 99%
“…Different cell wall nanomechanical properties (possibly stiffer, but more deformable leaves), brought about by EXLB8 overexpression, and consequently, possibly by other six endogenous EXL genes, was suggested as responsible of the phenotype hampering a successful infection. Various biotic and abiotic stress genes of the jasmonate, ethylene and abscisic acid pathways were also induced, activating a more general and unspecific priming of the host against pathogens with important lifestyle differences ( Brasileiro et al, 2021 ). Contrarily, A. thaliana EXLA2 down-regulation provides resistance to B. cinerea and oxidative stress, although roots become sensitive to salt and cold when the medium contains ABA ( Abuqamar et al, 2013 ).…”
Section: Expansins In Susceptibility To Infectionmentioning
confidence: 99%